Process-parameter-interface model for design management - Chua, D. K. H. (2013)
This paper presents a framework for managing the architecture/engineering/construction design process. The framework, called the process-parameter-interface (PPI) model, tries to address the design management issues of improved design process scheduling and efficient collaboration. The model comprises three main components—a design parameter vocabulary, in the form of a design dictionary; an interface; and an engine—that help to address these issues. In addition, the model promotes flexibility of design work flow, enables proactive collaboration, is implementable over the Internet, and is information-centric. The paper concludes with a case study for the design of a conference room to illustrate the functioning of the PPI model and the role of its components.